The Description of Factors Causing Pneumonia in Toddlers at Rose Room of Kendari City Hospital - Sunarya Sunarya; Hasrima Hasrima; Kemal Idris Balaka; Muhammad Uksim (KLASICS, 2023)
Pneumonia is the most common disease affecting infants and children globally. It is the most common cause of under-5 (U-5) death and contributed to 15% of U-5 deaths in 2017, killing an estimated 808,920 children. World Health Organization (WHO) data showed that acute respiratory infections (ARI) are the second most common cause of disability-adjusted life years lost worldwide. During the Millennium Development Goals era from 2000 to 2015, WHO-led ARI control programs reduced the burden of pneumonia deaths from 1.7 million annual cases to 0.9 million, a reduction of 30% in load. At the same time, the pneumonia mortality rate decreased by almost 51%. This study aims to describe the factors that cause pneumonia in the rose room of the Kendari City Hospital from May to June 2022. This research is a descriptive study with a total sample of 27 toddlers suffering from pneumonia. The results of this study show that the proportion of exclusive breastfeeding for most toddlers has received exclusive breastfeeding, namely 14 toddlers (51.9%). Toddlers with pneumonia are dominated by families with a smoking history, namely 23 people (85.2%). Based on the immunization history of pneumonia sufferers with immunization status dominated by incomplete immunization, as many as 15 people (55.6%). Based on the research results, it is recommended that people live a healthy lifestyle by not consuming cigarettes in the home environment or when they are close to toddlers.